Gender-Dependent Modulation of Alzheimer’s Disease by Brain Ischemia. Comment on Lohkamp et al. Sex-Specific Adaptations in Alzheimer’s Disease and Ischemic Stroke: A Longitudinal Study in Male and Female APPswe/PS1dE9 Mice. Life 2025, 15, 333 - Ryszard Pluta (Life)
This comment focuses on the contribution of experimental brain ischemia to the overwhelming incidence of Alzheimer’s disease in women as presented by Lohkamp et al. in Life 2025, 15, 333. The authors showed that in Alzheimer’s disease and ischemic stroke there are sex-dependent adaptations in the form of cross-links and vice versa. It was emphasized that the high longevity of women in itself does not explain the mechanisms underlying the biological differences between the sexes causing a female predominance in the development of Alzheimer’s disease. Differences were demonstrated between males and females: female APP/PS1 mice had greater amyloid deposition, hyperactivity, lower body weight, and reduced cerebral blood flow, as well as less neuroinflammation, which the authors suggest may have potential neuroprotection. It should be noted that some of the information presented in the article by Lohkamp et al. raises more questions than answers. Therefore, future studies should consider, for example, studies using single-cell technologies that can provide insight into the timing and sequence of cellular dysfunctions across sexes and analyze the continuity of changes over time, starting from short-term observations of a few days and ending with long-term observations of a year or more, to assess the continuity and differentiation of changes.